Facebook me!: Initial insights in favour of using social networking as a tool for translator training - Desjardins, Renée (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper argues in favour of integrating and using online social networking, more specifically Facebook, within the translation classroom. This has numerous benefits in terms of aptly preparing trainees for the marketplace and also helping to foster a classroom community by encouraging a collaborative learning environment. A descriptive analysis of five undergraduate courses suggests that using online social networking as a teaching strategy has a significant impact: from engaging students through collaborative translation projects, to peer-reviewing assignments, to establishing ‘telepresence’, Facebook allows the trainer to ‘connect’ the classroom.